Relationship of the Application of Block System Learning and Motivation to Learning with Learning Outcomes of Productive Vocational Light Vehicle Engineering Subjects - Wahyudiyanto Wahyudiyanto; Pairun Roniwijaya (Jurnal Taman Vokasi, 2018)
This study is a descriptive correlative study that aims to determine: (1) the relationship between the application of block system learning and learning achievement in productive subjects, (2) the relationship between learning motivation and learning achievement on productive subjects, (3) the relationship between the application of learning block system and learning motivation with learning achievement on productive subjects. The research sample was taken by random sampling technique as many as 90 students. The data collection technique uses a questionnaire for the variable implementation of block system learning and learning motivation and documentation for learning achievement variables. Test the validity of the instrument using product moment correlation and reliability using Cronbach's alpha. For the research hypothesis tested by product moment analysis techniques and double predictor multiple regression analysis. The results showed that: 1) there is a positive  and  significant  relationship  between  the  application  of  system  block  learning  (x1)  and learning outcomes (y) as evidenced by the correlation index of 0.914 and the relationship between the two can be shown in the regression line equation y = 33.849 + 0.633x1, 2) there is a positive and significant relationship between learning motivation (x2) and learning outcomes (y) as evidenced by a correlation index of 0.948 and the relationship between the two can be shown in the regression line equation  y = 31,552  +  0,685x2,  3) there is  a positive relationship  and  significant  between  the application of block system learning (x1) and learning motivation (x2) with learning outcomes (y) proved by the correlation index of 0.752 and the relationship between the two can be shown in the regression line equation y = 30.906 + 0.156x1 + 0.533x2.